2016
DOI: 10.3389/fnhum.2016.00528
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Causal Modeling of Hippocampal Links within the Human Default Mode Network: Lateralization and Computational Stability of Effective Connections

Abstract: The purpose of this paper was to study causal relationships between left and right hippocampal regions (LHIP and RHIP, respectively) within the default mode network (DMN) as represented by its key structures: the medial prefrontal cortex (MPFC), posterior cingulate cortex (PCC), and the inferior parietal cortex of left (LIPC) and right (RIPC) hemispheres. Furthermore, we were interested in testing the stability of the connectivity patterns when adding or deleting regions of interest. The functional magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 59 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…Remarkably, the within-network connectivity was very similar when networks were estimated separately compared to networks as a whole (compare e.g., Figure 5 and 6). This was also found by Ushakov et al (2016), who showed that connectivity within the core DMN was very similar when either left or right hippocampus was included in the network. This shows that group-level resting-state DCM results are quite robust against addition of extra networks and regions.…”
Section: Discussionsupporting
confidence: 73%
“…Remarkably, the within-network connectivity was very similar when networks were estimated separately compared to networks as a whole (compare e.g., Figure 5 and 6). This was also found by Ushakov et al (2016), who showed that connectivity within the core DMN was very similar when either left or right hippocampus was included in the network. This shows that group-level resting-state DCM results are quite robust against addition of extra networks and regions.…”
Section: Discussionsupporting
confidence: 73%
“…Both studies found reciprocal positive connectivity between IPC, and positive projections from lateral to medial brain regions. Ushakov et al (2016) showed that adding extra regions (i.e., left and right parahippocampal gyri) to the four-region DMN did not have a substantial impact on its effective connectivity pattern. Zhou et al (2018) showed that the salience and dorsal attention network have a negative influence on the core DMN, while the converse influence was slightly positive.…”
Section: Introductionmentioning
confidence: 99%
“…Most research using empirical data has focused on effective connectivity within the default mode network (e.g., Razi et al, 2015;Sharaev et al, 2016;Ushakov et al, 2016;Zhou et al 2018). Both Razi et al (2015) and Sharaev et al, 2016 estimated connectivity within the 'core' DMN, which included left and right intraparietal cortices (IPC), medial prefrontal cortex (mPFC), and posterior cingulate cortex (PCC).…”
Section: Introductionmentioning
confidence: 99%
“…This convergence of methodologies seems to lead to a convergence in results. To be more specific, I will address several implications of the recent discovery which demonstrated a profound asymmetry in effective (cause-and-effect) connections between the left and right hippocampi within the human default mode network, or DMN (Ushakov et al, 2016). The latter is a set of functionally and structurally connected brain areas that are activated at rest and deactivated by external stimulation.…”
mentioning
confidence: 99%
“…Recent neuroimaging studies of the DMN bring together both concepts by showing that activity around the right temporoparietal junction is the best predictor of working memory scores (Markett et al, 2017). This region in turn is the main input pathway to the right hippocampus within the DMN connectome (see Ushakov et al, 2016Ushakov et al, , velichkovsky et al, 2017.…”
mentioning
confidence: 99%